Effective Methods for Assessing Creativity and Technological Competencies - Sharipova Gulshoda Bahriddinovna (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores effective methods for assessing students’ creativity and technological competencies. Proper evaluation techniques enable educators to measure both the technical skills and innovative thinking of students, ensuring balanced development in creative and technological domains. The study emphasizes that structured assessment strategies, including project-based evaluation, digital portfolios, and performance tasks, enhance student motivation, support independent learning, and promote continuous improvement.